Challenges in Implementation of ICT for the Budget Accountability and Development of Budget Information Literacy - Hastjarjo, Sri; Wahyunengseh, Rutiana Dwi (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2013)
In the case of Karanganyar Regency, this study identify that although the public aspire to have an adequate understanding about the APBD, the access for obtaining the information is very limited. Data collection methods used in this research were: (1) documents study on the Local Government Development Plan (RKPD) and the Regional Budget (APBD); (2) semi open-ended questionnaires; (3) in-depth interviews; and (4) focus group discussions. The data then analyzed using descriptive analysis and interpretive analysis methods. This paper recognizes the potency of ICT in developing the forum for public access and deliberation related to the budget information; while also identifies the challenges facing the implementation of ICT for the local budget accountability and the development of budget information literacy among the public.